Simultaneous Estimation of Cinnamaldehyde and Eugenol in Essential Oils and Traditional and Ultrasound-Assisted Extracts of Different Species of Cinnamon Using a Sustainable/Green HPTLC Technique - Ahmed I. Foudah; Faiyaz Shakeel; Mohammed H. Alqarni; Samir A. Ross; Mohammad A. Salkini; Prawez Alam (Molecules, 2021)
A wide range of analytical techniques are reported for the determination of cinnamaldehyde (CCHO) and eugenol (EOH) in plant extracts and herbal formulations either alone or in combination. Nevertheless, sustainable/green analytical techniques for the estimation of CCHO and EOH either alone or in combination are scarce in the literature. Accordingly, the present research was carried out to establish a rapid, highly sensitive, and sustainable high-performance thin-layer chromatography (HPTLC) technique for the simultaneous estimation of CCHO and EOH in the traditional and ultrasound-assisted methanolic extracts of Cinnamomum zeylanicum,C. burmannii, and C. cassia and their essential oils. The simultaneous estimation of CCHO and EOH was performed through NP-18 silica gel 60 F254S HPTLC plates. The cyclohexane/ethyl acetate (90:10, v v−1) solvent system was optimized as the mobile phase for the simultaneous estimation of CCHO and EOH. The greenness score of the HPTLC technique was predicted using AGREE software. The entire analysis was carried out at a detection wavelength of 296 nm for CCHO and EOH. The sustainable HPTLC technique was observed as linear in the range 10–2000 ng band−1 for CCHO and EOH. The proposed technique was found to be highly sensitive, rapid, accurate, precise, and robust for the simultaneous estimation of CCHO and EOH. The content of CCHO in traditional methanolic extracts of C. zeylanicum,C. burmannii, and C. cassia was found to be 96.36, 118.49, and 114.18 mg g−1, respectively. However, the content of CCHO in ultrasound-assisted methanolic extracts of C. zeylanicum,C. burmannii, and C. cassia was found to be 111.57, 134.39, and 129.07 mg g−1, respectively. The content of CCHO in essential oils of C. zeylanicum,C. burmannii, and C. cassia was found to be 191.20, 214.24, and 202.09 mg g−1, respectively. The content of EOH in traditional methanolic extracts of C. zeylanicum,C. burmannii, and C. cassia was found to be 73.38, 165.41, and 109.10 mg g−1, respectively. However, the content of EOH in ultrasound-assisted methanolic extracts of C. zeylanicum,C. burmannii, and C. cassia was found to be 87.20, 218.09, and 121.85 mg g−1, respectively. The content of EOH in essential oils of C. zeylanicum,C. burmannii, and C. cassia was found to be 61.26, 79.21, and 69.02 mg g−1, respectively. The amounts of CCHO and EOH were found to be significantly higher in ultrasound-assisted extracts of all species compared to its traditional extraction and hence ultrasound extraction has been proposed as a superior technique for the extraction of CCHO and EOH. The AGREE analytical score of the present analytical technique was predicted as 0.75, suggesting excellent greenness profile of the proposed analytical technique. Based on all these observations and results, the proposed sustainable HPTLC technique can be successfully used for the simultaneous estimation of CCHO and EOH in different plant extracts and herbal products.